Multiple magma reservoirs for the 1707 eruption of Fuji volcano, Japan - Yoshimoto, Mitsuhiro (Proc Jpn Acad Ser B Phys Biol Sci, 2004)
In 1707, approximately 0.7 km(3) of magma erupted from new vents on the southeastern slope of Fuji volcano. The air-fall clasts of this explosive eruption are composed of vesicular dacite pumice, andesitic dense scoria, basaltic dense scoria, and vesiculated basalt scoria, stratified from bottom to the top of the fallout unit. Some compositional gaps are found in the variation from basalt to dacite indicating that three independent magmas, basalt, andesite and dacite, existed just prior to the eruption. Andesite and dacite magmas are mixed just prior to or during the eruption showing a linear two component mixing in the major and trace element concentration. Basalt in the later stage of the eruption shows no compositional affinity with the above two magmas. Basalt magma might have acted as a heat source to remobilize the andesite and dacite magmas, and the explosive eruption of basalt could have been caused by the abrupt pressure release due to precursory mixing and eruption of dacite and andesite magmas.